2017
DOI: 10.1101/201384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancestral perinatal obesogen exposure results in a transgenerational thrifty phenotype in mice

Abstract: Ancestral environmental exposures to non-mutagenic agents can exert effects in unexposed descendants. This transgenerational inheritance has significant implications for understanding disease etiology. The obesogen hypothesis proposes that exposure to obesogenic chemicals can lead to increased adiposity, in vivo. Here we show that exposure of F0 mice to the obesogen tributyltin (TBT) throughout pregnancy and lactation predisposes unexposed F4 male descendants to obesity when dietary fat is increased. Analyses … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…Recent studies have established that obesogens can alter metabolic "set points" leading to obesity later in life, particularly when dietary composition or caloric intake is changed. 55,56 Obesogens do not necessarily induce obesity alone, but they can alter developmental programming, affecting nuclear factors or other endocrine pathways during development in ways that lead to obesity later in life. It is important to note that not all EDCs are obesogens and not all obesogens are EDCs; there are dietary obesogens such as refined sugars that may not meet the strict definition of an EDC, but which are definitely obesogens.…”
Section: The Obesogen Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have established that obesogens can alter metabolic "set points" leading to obesity later in life, particularly when dietary composition or caloric intake is changed. 55,56 Obesogens do not necessarily induce obesity alone, but they can alter developmental programming, affecting nuclear factors or other endocrine pathways during development in ways that lead to obesity later in life. It is important to note that not all EDCs are obesogens and not all obesogens are EDCs; there are dietary obesogens such as refined sugars that may not meet the strict definition of an EDC, but which are definitely obesogens.…”
Section: The Obesogen Hypothesismentioning
confidence: 99%
“…105 Exposure of F0 female mice to TBT throughout pregnancy and lactation led to males of the unexposed F4 generation gaining weight very rapidly when dietary fat was increased; they retained much of this extra fat even after their chow was returned to the previous low-fat diet. 55 The animals also overexpressed leptin, and the authors inferred they were leptin-resistant. 55 A very important recent study in humans showed that caloric restriction in a clinical setting led to weight loss, irrespective of the type of diet but that individuals regained weight at different rates when dieting was ceased.…”
Section: Modulate Metabolic Set Points?mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects led to a more significant decline in basal metabolic rate during weight loss and less increase in basal metabolic rate during weight regain. Chamorro-Garcia et al 39 showed that ancestral exposure to tributyltin resulted in animals (four generations later) that were more sensitive to gaining weight when they were switched to a high-fat diet compared to control animals. When these animals were returned to a standard control diet, they lost weight more slowly than control animals.…”
Section: F I G U R E 2 Transgenerationalmentioning
confidence: 99%
“…51 Thus, a recent study, presented at PPTOX VI, showed that transgenerational inheritance of obesity was observed from perinatal tributyltin exposure, apparently mediated through altered higher-order chromatin organization. 52 Reorganized chromatin, transmissible through meiosis and mitosis, can in turn influence DNA methylation at accessible sites that modified transcription, suggesting that this is a proximal event. These new mechanistic insights indicate that a revision of research paradigms and interpretation is required.…”
Section: Mechanistic Insightsmentioning
confidence: 99%